Community driven solutions for TVET self employment Research based SULAM - Hadijah, Ahmad (UMPSA, 2024)
A TVET graduate tracer study conducted in 2020 revealed that the Ministry of Rural and Regional Development (MRRD) produced the highest number of entrepreneurs, 44.6% of them earning incomes below RM1000 from automotive repair and service workshops and 76.7% from tailoring and clothing manufacturing.